Bilateral Vocal Fold Paralysis in Myasthenia Gravis: A Case Report and Literature Review - Nelke, Christopher (Front Neurol, 2020)
To prevent severe and potentially life-threatening consequences of bilateral vocal fold paralysis (BVFP), the identification and management of reversible causes is pivotal. Myasthenia gravis (MG) presenting with BVFP is rarely reported and remains incompletely understood. Although symptom control is achievable for most MG patients with sufficient therapy, atypical clinical presentation such as BVFP might preclude diagnosis and thus effective treatment. Here, we present a case of BVFP as leading manifestation of MG successfully treated with plasmapheresis. Moreover, we performed a literature review of the few existing cases reported between 1980 and 2020 indicating that elderly patients are particularly at risk for MG presenting with severe BVFP and that edrophonium testing with fiber optic endoscopic evaluation of swallowing (FEES) might be valuable for establishing the diagnosis. We conclude that clinicians should consider MG as possible and reversible cause for BVFP.